CASE REPORT: "APPENDICITIS" POST ABORTION - Siu, Alejandro (2015)
This case corresponds to the unusual and infrequent one of the most common conditions that warrant acute abdomen surgery presentation. A patient having a history of abortion maneuvers have been conducted eleven days before, presented to emergency with cellulitis on the right side radiating to the back-lumbar region, forming an area of approximately 30 x 15 cm .; not referring other symptoms. Twenty four hours later develop signs of acute abdomen, forty eight hours after an examination under anesthesia and curettage laparotomy was performed; the cause of all this picture: retrocecal perforated appendicitis.